Does the financial market believe in the Phillips Curve? Evidence from the G7 countries - Ralf Fendel; Eliza M. Lis; Jan-Christoph Rülke (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2008)
This paper uses monthly survey data for the G7 countries for the time period 1989 - 2007 to explore the link between expectations on nominal wages, prices and unemployment rate as suggested by the traditional and Samuelson-and-Solow-type Phillips curve. Three major findings stand out: First, we find that survey participants trust in the original as well as the Samuelson-and-Solow-type Phillips curve relationship. Second, we find evidence in favor of nonlinearities in the expected Samuelson-and-Solow-type Phillips curve. Third, when we take into account a kink in the expected Phillips curve indicating that the slope of the Phillips curve differs during the business cycle, we find strong evidence of this feature in the data which confirms recent the- oretical discussions in the literature that the Phillips curve is flatter in case of an economic downturn.
Keywords: C23; E37; E31; 330; Phillips curve; Forecasting; Panel data model; Phillips-Kurve; Prognoseverfahren; Panel; G-7-Staaten